Beyond Einstein : the cosmic quest for the theory of the universe - Kaku Michio (OUP, Anchor Books, 1999)
Beyond Einstein takes readers on an exciting excursion into the discoveries that have led scientists to the brightest new prospect in theoretical physics today -- superstring theory. What is superstring theory and why is it important? This revolutionary breakthrough may well be the fulfillment of Albert Einstein's lifelong dream of a Theory of Everything, uniting the laws of physics into a single description explaining all the known forces in the universe